Cognitive Dysfunction After Multiple Surgery (Eurasian Medical Research Periodical, 2022)
The state of cognitive function was studied in 121 patients aged 20 to 59 years in the postoperative period under general anesthesia after various surgical interventions. Of these, 63 patients were after one operation and 58 patients after multiple operations. POCD was diagnosed in 26 (41.3%) of 63 patients of group 1 after one operation, then after multiple operations in 45 (77.3%) of 58 patients of group 2, that is, almost twice as many. This study confirms that multiple surgery may be a factor in the development of cognitive dysfunction